2022
DOI: 10.3389/feart.2022.931466
|View full text |Cite
|
Sign up to set email alerts
|

A novel evaluation method of mining goaf ground activation under high-speed railway load

Abstract: With the continuous improvement of infrastructure, some high-speed railway lines will inevitably cross the goaf ground, and there is less research on the safety of high-speed rail construction in goaf ground. To make a reasonable and accurate safety evaluation of the high-speed railway construction in the mine goaf ground, machine learning combined with numerical simulation is used to evaluate the safety depth of goaf under the impact of high-speed railway load. An optimal algorithm is selected among BP, RBF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The stability of a foundation can be quantitatively evaluated before a new building is built on the ground of an old goaf according to the spatial relationship between the depth of the load influence and the height of the caving fracture zone of coal seam (Xu et al, 2014;Liu et al, 2015;Zhang et al, 2019). Ren et al (2022) chose an optimal algorithm to calculate the influence depth of the train load and the development height of the caving fracture zone. The results showed that a 'particle swarm optimization' -'radial basis function' neural network model obtained the smallest error, and the prediction was the most accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of a foundation can be quantitatively evaluated before a new building is built on the ground of an old goaf according to the spatial relationship between the depth of the load influence and the height of the caving fracture zone of coal seam (Xu et al, 2014;Liu et al, 2015;Zhang et al, 2019). Ren et al (2022) chose an optimal algorithm to calculate the influence depth of the train load and the development height of the caving fracture zone. The results showed that a 'particle swarm optimization' -'radial basis function' neural network model obtained the smallest error, and the prediction was the most accurate.…”
Section: Introductionmentioning
confidence: 99%